Degrees in Revolution and for the Revolution’s Sake: The Educational Experience of Polish Communists before 1939 - Bertram, Łukasz (Państwowe Wydawnictwo Naukowe, 2021)
This paper identifies the most significant patterns of educational experience among members of the interwar Polish communist movement. The first part of the article covers the experiences that communists shared with other representatives of the social strata from which they originated: the reproduction of the social structure or their overcoming of it in the form of social advancement. It also discusses the importance of educational barriers and opportunities as factors facilitating the emergence of attitudes of radical contestation of the socio-political order. The second part identifies educational experiences that were directly related to involvement in an illegal, subversive and repressed political current, and the diverse, sometimes paradoxical consequences of that involvement for representatives of different social strata. It traces the transformations of the communist habitus and proposes the concept of ‘clandestine white-collar workers’. The article concludes that there were two patterns in the pursuit of education among the communists: acquiring a degree in revolution or for the sake of the revolution.
p. 215-237
Keywords: communism - Poland - 1900-1945; Communist Party of Poland (Komunistyczna Partia Polski); communism and education - Poland; socialization - Poland - 1900-1945; habitus (sociology); cultural capital